The Effects of Molybdenum and / or Sulfur Supplementation on the Mineral Status of Plasma and Liver of Sheep Fed Palm Kernel Cake - Li, Juan (1999)
Although palm kernel cake (PKC) has been widely used as a feed for large ruminant, its high copper (Cu) content is potentially poisonous to sheep and possibly goats. It is well known that sheep are extremely intolerant of Cu toxicity. Sheep fed high levels of PKC, showed high levels of Cu in the liver, which caused jaundice and liver damage. Some studies showed that molybdenum (Mo) and/or sulfur (S) could form complexes with Cu to make Cu unavailable, hence reducing the accumulation in the liver. However, the optimum amount of S and Mo need to be added to PKC has not been established. In the present study, from 80 six months to one-year-old Malin cross sheep, 72 were selected and allocated randomly into 9 groups with 8 animals each. The animals were offered PKC pellet (96-97%) supplemented with different levels of S and Mo, hence, Diet A (Mo, 13ppm), Diet B (Mo, 26ppm), Diet C (52ppm), Diet D (Mo, 1 03ppm), Diet E (S, 4400ppm, Mo, 13ppm), Diet F (S, 4400ppm , Mo, 26ppm), Diet G (S, 4400ppm, Mo, 52ppm), Diet H (S, 4400ppm, Mo, 103ppm), Diet I (S, 4400ppm). The feeding trial lasted 6 months. The animals were slaughtered in two g roups, i.e. , at the end of 3 months and 6 months of the feeding trial respectively. When the animals were slaughtered, their livers were removed, prepared and were analyzed for mineral concentration. The blood was collected from the jugular vein of each sheep in heparinized vacuum tubes and centrifuged to obtain plasma once every 2 months throughout the trial. The plasma was prepared for the analyses of the mineral content and this was carried out by Atomic Absorption Spectrophotometer (AAS). The results showed that Mo when combined with S and Mo alone in high levels were more efficient in reducing the liver Cu levels in sheep than Mo in low levels or S. However, except for Ca, other elements analyzed also showed different variations among treatments and the initial values. The plasma minerals showed some differences from that of liver minerals. Again, except for Ca, other elements presented some changes over time. The causes of the above may be complicated, however, the major reason considered is the dietary treatments. It is evident in this study that Mo and / or S supplementation have prevented the sheep from chronic Cu toxicity as caused by PKC, and the animals survived between 3-6 months of feeding trial. When those treatments were compared, all Mo + S groups seem to be more efficient in lowering the liver Cu levels.